2021
DOI: 10.3389/fmicb.2021.686509
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Strategies for the Bioremediation of the Phenylurea Herbicide Diuron

Abstract: Diuron (DUR) is a phenylurea herbicide widely used for the effective control of most annual and perennial weeds in farming areas. The extensive use of DUR has led to its widespread presence in soil, sediment, and aquatic environments, which poses a threat to non-target crops, animals, humans, and ecosystems. Therefore, the removal of DUR from contaminated environments has been a hot topic for researchers in recent decades. Bioremediation seldom leaves harmful intermediate metabolites and is emerging as the mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 136 publications
(242 reference statements)
0
22
0
Order By: Relevance
“…(2021) reported changes in soil microbial community activity by repeated application of dimethachlor and linuron. Biodegradation of phenylurea herbicide diuron was accomplished by the beta‐oxidation pathway by the soil bacteria (Li et al., 2021). Beta‐ketoadipate pathway was used by Acinetobacter tandoii to degrade phenolic compounds (Van Dexter & Boopathy, 2019; Van Dexter et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…(2021) reported changes in soil microbial community activity by repeated application of dimethachlor and linuron. Biodegradation of phenylurea herbicide diuron was accomplished by the beta‐oxidation pathway by the soil bacteria (Li et al., 2021). Beta‐ketoadipate pathway was used by Acinetobacter tandoii to degrade phenolic compounds (Van Dexter & Boopathy, 2019; Van Dexter et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…LOC_Os04g38870 is one of the highest transcription levels whose encoding monooxygenase GF14b is regulated by methyl jasmonate and involved in rice tolerance to abiotic stresses . Transformation of DU to 3,4-dichloroaniline via hydrolase and esterase is well known; however, few studies were reported in plants. In rice, plenty of genes encoding hydrolase and esterase like LOC_Os04g56930 and LOC_Os05g30760 exhibited a positive dose–response relationship with DU levels (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…All sorbents had the aptitude to eliminate Cd(II) from wastewater samples, and improved elimination happened when fungal cells were immobilized in comparison to free cells. Cd(II) elimination by free and immobilized fungal biomass on loofa sponge from real wastewater samples is presented in the form of Figure 4a (Ali et al, 2021), where PEN is for ‘free Penicillium chrysogenum ’, PEN‐ILS is for ‘ Penicillium chrysogenum immobilized on loofa sponge’, CEP is for ‘free Cephalotheca foveolata ’, CEP‐ILS is for ‘ Cephalotheca foveolata immobilized on loofa sponge’. Sample (1) was wastewater taken from General Motors Factory in Giza, and sample (2) was wastewater taken from Egyptian Plastic and Electricity Factory in Cairo.…”
Section: Mycoremediation Of Heavy Metals and Environmental Restorationmentioning
confidence: 99%
“…Similarly, higher efficiency was attained by loofa sponge‐immobilized biomass of C. foveolata in comparison to the free C. foveolata usage, with the elimination of 46.8% and 40.0% of Cd(II), respectively. In the sample 2, greater sorption capacity was provided by the usage of loofa sponge‐immobilized biomass consisting of P. chrysogenum and C. foveolata in comparison to the usage of the free fungal species, where they eliminated 54.2% and 50.0% of Cd(II) in compared to 42.2% and 43.0%, respectively (Ali et al, 2021).…”
Section: Mycoremediation Of Heavy Metals and Environmental Restorationmentioning
confidence: 99%